Original single walled nanotubules based on weakly interacting covalent mineral polymers, (1)(infinity)[Nb2PS10-] in N-methylformamide - Camerel, F.; Gabriel, J.C.P.; Batail, P.; Davidson, P.; Lemaire, B.; Schmutz, M.; Guilk-Krzywicki, T.; Bourgaux, C. (Nano Letters, 2002)
This paper reports the synthesis of a new one-dimensional phase, NaNb2PS10, which is found to be soluble in polar organic solvents such as N-methylformamide (NMF) or dimethylformamide (DMF). Small-angle X-ray scattering (SAXS) and transmission electron microscopy (TEM) studies have revealed that these covalent polymer coils fold into unprecedented single wall monodispersed nanotubules in NMF (external diameter 10 nm; wall thickness = 1.6 nm; length from 10 nm to over one micrometer). Cooperative weak bonds involving the hydrogen bond donor/acceptor ability of the primary amide solvent at the organic-inorganic interface are likely to assemble the flexible, charged covalent mineral polymer and indeed stabilize the nanotubule wall.